Patient Case Report Daptomycin Holiday—A Daptomycin Dosing Strategy for Asymptomatic Increases in Creatine Phosphokinase Levels. (February 2022) - Koh, Leroy; Shah, Punit J.; Aly, Sarfraz
Daptomycin possesses excellent activity against many multidrug-resistant gram positive organisms. However, a side effect of concern with daptomycin is skeletal muscle injury, which is manifested in the form of elevated creatine phosphokinase (CPK). Management of such CPK elevations has traditionally been discontinuation of the offending agent, with many studies showing a resolution of a normal CPK level within 1 week of discontinuation and no long term adverse effects. Nevertheless, the question remains if daptomycin can be successfully restarted in such patients. Here, we present a case of a "daptomycin holiday" in which daptomycin was withheld upon CPK elevation and successfully reintroduced to the patient's regimen again after several days without further elevation of the CPK. The patient had a peak CPK of 2, 557 U/L, and had no associated symptoms. A hypothesis for this holiday could be the adaptability of the skeletal muscle myocytes, in which the extra period between doses may allow for additional recovery of the membrane structure to further daptomycin exposure. Giving an asymptomatic patient with elevated CPK level, a short daptomycin holiday to allow for the CPK level to trend downward before resuming daptomycin therapy could be a potential strategy in patients for whom continuing daptomycin is still preferred.